A BEHAVIORAL PERSPECTIVE ON LABOR SUPPLY ANALYSIS - Bakir, Zeynep Sumeyra; Sahin, Senem Cakmak (MEHMET AKIF ERSOY UNIV, 2022)
The behavioral economics approach expands its domains in many areas such as consumer theory, game theory, financial markets, decision-making processes, and public policies. Behavioral finance, behavioral public policies, behavioral game theory may expressed as the outputs of the effect of behavioral economics. The consideration of the labor market through the behavioral economics approach is important for the development of the understanding of the field. The purpose of this paper is to point out the potentials of behavioral labor economics and analyze the labor supply within the framework of behavioral economics. In this regard, the scope of the study is limited by the labor supply. The findings of the study as follow: (i) full rationality is not valid to an accurate analysis in terms of labor supply decisions (ii) there are behavioral and cognitive biases in the labor market (iii) the behavioral economics approach has important contributions to understanding decision processes and behaviors of the labor supply (iv) it has a potential to improve theories in the field of labor and to develop alternative theories, (v) the labor economy is open to integrating and adapting to the approach of behavioral economics.
Keywords: Labor Economics; Behavioral Economics; Labor Supply; Rationality; Behavioral Labor Economics; WAGE RIGIDITY; ECONOMICS; FAIRNESS; MARKET; FOUNDATIONS; PSYCHOLOGY; Business & Economics